DEVELOPMENT OF TRIANGGLE AND RECTANGULAR SUBJECT OF MATHEMATICAL POCKETBOOK FOR CLASS VII STUDENTS OF SMP / MTs - Ratna Wahyu Utami; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
The background of this study due to the unavailability of the pocketbook as a source of learning. This study aims to prepare and develop teaching material in the form of a mathematics pocketbook for subject matter triangles and rectangular to class VII Junior High School (SMP/MTs) to determine the feasibility of teaching materials. The research was carried out using a model of the development ofÂ Research and Development (R & D). The measures include the development of two aspects, namely the development of mathematics and pocketbooks' feasibility. The development of a mathematical pocketbook covers the preparation, implementation, testing, and revision. The feasibility of mathematics includes both material and media worthiness. Instruments used questionnaire matter experts, media experts, and student responses to assess the feasibility of pocketbooks. They were analyzed using qualitative descriptive. Research Subjects are subject VIIIth grade students SMP Negeri 3 Kasihan and MTs Muhammadiyah Karangkajen. Â Results of research development of mathematics pocketbook for subject matter triangle and rectangular in class VII SMP / MTS obtained from the analysis of the average valuation matter experts by 69,67 with the category is very good, the average valuation by media expert is 90, 33 with the category is very good, and the average valuation student responses is 83.07 with the excellent category. It can be concluded that mathematics pocketbook with an excellent category, so it is feasible to use in the learning process.